SILIKON HASIL REDUKSI SILIKA DARI FLY ASH BATUBARA UNTUK PEMBUATAN HIDROGEN - Eti Nurmahdani; Robert Junaidi; Indah Purnamasari (KINETIKA, 2022)
Coal fly ash waste is a mineral residue in fine grains produced from the coal burning process from the coal-fired power plant. Coal fly ash contains chemical elements including silica (SiO2) which reaches 40%. Silica has many benefits in the industrial world, one of which can be used as a material for making silicone (Si). The purpose of this study is to make silicon and purify the resulting silicon with variations in the amount of reducers, and the application of silicon to make hydrogen with NaOH variations. In this study silicon insulation used silica:magnesium variations in a ratio of 1:0.5; 1:0,8 and 1:1. Furthermore, the variation of NaOH in the manufacture of hydrogen with concentrations of 2 M, 2.5 and 3 M. The methodology used is silica extraction by precipitation method, silicon isolation by metallothermal method, silicon purification with HCl and hydrogen manufacturing with NaOH. Silicone making is carried out by reducing silica with magnesium which is then in a furnace for 3 hours with a temperature of 650°C. The best result obtained at silicone manufacturing is a ratio of 1:1 with an intensity of 1905 cps and the yield obtained reaches 92%. Si 1:1 was then used for the manufacture of hydrogen and obtained the largest volume of 0.97 liters with a gas content of 2.647 ppm. Keywords: Silicon, Silica, Coal Fly Ash, Hydrogen, Metalothermal Method